(untitled) (Journal of Nepal Physical Society, 2020)
This work was mainly based on three interdependent parameters, which are temperature, emissivity and peak emission wavelength. Temperature is the primary parameter that determines how much light the filament gives off, and at what wavelengths. The work was focused on temperature determination of tungsten filament with different values of emissivity. The different values of emissivity taken for the work were 0.433, 0.431, 0.427, 0.421 and 0.415. Peak emission wavelength was calculated at different tungsten temperatures for different wattage bulbs which was in the order of 10-6m. 6, 60, and 500 watt bulb were taken for the work. The peak of the spectrum lay in the infrared region. Wien’s displacement law was used to calculate the value of peak emission wavelength. The work was based on theoretical model. Blackbody spectrum curve was used to analyze the emitted radiations from the bulb. In each spectrum curve, radiations having higher wavelengths were emitted in greater amount than the radiations having lower wavelength. Spectral radiance was found to be dependent upon both emissivity and power of the bulb. The area under the blackbody spectrum curve indicated the total number of emitted radiations and hence the total energy radiated across all wavelengths. The total energy emitted from tungsten filament was found to be increased rapidly with temperature. Brightness of the bulb increased with the increase in temperature of the tungsten. The peak in the blackbody spectrum curve shifts towards left, when temperature increased. There is a direct consequence of the brightness of bulb with the peak emission wavelength.